Peran Literasi dan Kearifan Lokal dalam Meningkatkan Kesiapsiagaan Siswa SMA Negeri 1 Bone Pantai Menghadapi Ancaman Bencana - Masruroh Masruroh; Sunarty Suly Eraku; Moch Rio Pambudi; Ninasafitri Ninasafitri; Ayub Pratama Aris; Ramla Hartini Melo (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2023)
Gorontalo is one of the areas in Indonesia that has the potential for natural disasters, so efforts are needed to minimize the impact of disasters. One effort to deal with the threat of disaster is to increase the role of literacy and local wisdom to provide an understanding of the hazards and impacts of disasters in disaster-prone areas. The purpose of this community service is to strengthen the role of literacy and local wisdom in increasing the preparedness of SMA Negeri 1 Bone Pantai students in facing the threat of disaster. The target of this activity is high school students. The method used in this community service activity is a quantitative approach with student participation, namely by involving students directly through mentoring during school service activities. The results of the pre-test, namely 50% of students understand the role of literacy and local wisdom and the results of the post-test show that 83% of students understand the role of literacy and local wisdom in increasing disaster preparedness. All students took part in strengthening the role of literacy and local wisdom enthusiastically through outreach and discussion. Thus strengthening the role of literacy and local wisdom in increasing disaster preparedness can be said to be good by providing socialization and concrete actions that will be remembered by students in disaster preparedness. This activity is expected to have a positive impact as an effort to increase the preparedness of SMA N 1 Bone Pantai District students. Gorontalo.